Leadership Strategies in Decision-Making for Senior High School Principals - Putri, Helena Anggraeni; Pisriwati, Siti Atwano; Siswanto, Deny Hadi (Journal of Organizational and Human Resource Development Strategies, 2024)
This study seeks to investigate the leadership approaches employed by the principal in managing disciplinary violations at Muhammadiyah Mlati Senior High School. Using a qualitative case study methodology, the research focuses on gathering perspectives from the principal, teachers, and students as key sources of information. Data was collected through interviews, observations, and document analysis, with triangulation used to ensure the accuracy and depth of the findings. The results highlight three key aspects of the principal's leadership in handling disciplinary matters. First, the decision-making process involves identifying and categorizing violations committed by both teachers and students, from minor to serious offenses, to determine suitable disciplinary measures. Second, the principal investigates the root causes of these violations to address the underlying issues contributing to rule-breaking. Third, the study demonstrates that the principal considers the broader effects of decisions on both students and teachers, emphasizing the importance of effective communication and socialization strategies to foster better discipline across the school. These leadership practices are crucial in creating a more disciplined and supportive learning environment.